Arcyria minuta - Krivomaz, Т. І.; Michaud, A.; Minter, D. W. (CABI, 2012)
Diagnostic features. Flat-topped, pink sporangia, each with a fixed capillitium, and capillitium thread marking more or less limited to cogs. Poorly developed sporocarps, or those with a non-expanded capillitium resemble A. cinerea (Bull.) Pers., but in A. cinerea sporangium colour is grey, and capillitium markings are densely spinulose. Sporangium colour in A. minuta is similar to that of A. pomiphomis (Leers) Rostaf., but A. minuta has larger sporocarps and cylindrical rather than subglobose sporangia.
Keywords: myxomycetes; міксоміцети; Arcyria minuta